The Mediating Roles Of Religious And Spiritual Coping Between Religiosity, Spirituality, And Depression Among Medical And Health Science Students. - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmad H.Osman, Rahmah; Abdul Razak, Abdul Latif; Allie, Nasreen; Ahmed, Mohamed Ayaaz; Jalaludin, Mohamad Afiudin; Mohd Kadri, Nursyuhaidah (Ubiquity Press Ltd , Unit 3.22, East London Works, 65-75 Whitechapel Road, LONDON, England, E1 1DU, 2022)
Introduction: Depression is a global mental health issue. Vulnerability for this condition increases in the university student population, specifically medical and health science disciplines. Previous evidence showed that religiosity and spirituality were inversely linked with depression. They have also been predominantly treated as one construct. Still, the mechanisms of these relationships are vague.